Sensores miniaturizados para COVID-19 e paracetamol: uma abordagem simples e de baixo-custo - Moreira, Nikaele Sousa (2024)
This work describes the development of miniaturized sensors on accessible and low-cost substrates to detect the spike protein (S) of the SARS-CoV-2 virus and paracetamol in whiskey samples. Protein S is a marker associated with COVID-19, which is present on the external part of the virus and has an affinity with the human angiotensin-converting enzyme 2 (hACE2), allowing the infection of human cells. Therefore, its detection is of great importance for an early diagnosis of the disease. In this context, polyester microplates were developed for the colorimetric detection of this protein in biological samples based on a direct ELISA assay for rapid detection and with less use of reagents, in addition to good clinical accuracy. A linear range was obtained in protein S concentrations of 0-10 μg mL-1, with a coefficient of determination (R2) equal to 0.991 and a limit of detection 0.44 μg mL-1. The proposed methodology revealed satisfactory intraplate and interplate repeatability with standard deviation values below 7.7%. Thirty-seven saliva and swab samples from positive and negative patients were evaluated for the presence of the virus. The results were consistent with the RT-PCR method, showing 100% sensitivity and 85.71% specificity for saliva samples. For nasopharyngeal samples, sensitivity was 90% and specificity was 100%. In addition, it revealed diagnostic accuracy above 94%, indicating that the proposed method can predict more than 94% of the samples correctly. Adulteration of whiskey is a common practice in nightclubs due to the high cost of these original drinks. Counterfeiters often add medications or pharmaceuticals to mask the effects of a hangover, for example, paracetamol, as it is an over-the-counter analgesic indicated for the treatment of headaches. Therefore, distance-based detection of paracetamol in whiskey samples using a paper-based microfluidic analytical device (μPAD) is imperative since the use of paper substrate offers excellent benefits, such as accessibility, portability, and the ability to detect paracetamol without expensive instrumentation. Optimal detection conditions were achieved by introducing 5 μL of a mixture containing 7.5 mmol L-1 of Fe(III) and K3[Fe(CN)6] into the detection zone, together with 12 μL of whiskey samples into the sample zone. The method showed linear behavior in the 15 to 120 mg L-1 concentration range, with R2 equal to 0.998. Paracetamol was quantified in spiked samples using the proposed method, and the results were compared with those of a spectrometric method. No significant differences were observed at the 95% confidence level. The method determined approximately 1 drop of the drug paracetamol of 200 mg mL-1 in 1 L of solution, demonstrating excellent sensitivity. Therefore, the proposed methods are alternatives for practical, simple and economical analyses and reduce the consumption of samples, reagents and waste. Then, they have great potential to be used in the field for clinical applications in diagnosing COVID-19 and forensic applications for detecting paracetamol in beverages.